Długoterminowa efektywność inwestycji w akcje spółek debiutujących na GPW - Czekaj, Karolina (Long-run performance of IPOs on WSE, 2006)
This article surveys the long-run underperformance of initial public offerings on the Polish stock exchange. Buying new issued stocks on the first day of their quotation and holding them for 3 years turned out to be an unsuccessful investment strategy. The findings are consistent with the research of this phenomenon on other world stock exchanges. This paper seeks for an explanation of this poor long-run performance by reviewing and examining the most important hypotheses of this puzzle: a) The divergence of opinion hypothesis; b) The windows of opportunity hypothesis; c) The impresario hypothesis and d) The window dressing hypothesis.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1133, s. 61-68